Comparative government and politics : an introduction - Hague, Rod.; Harrop, Martin (New York : Palgrave Macmillan, 2010)
"Long established as the leading text in the field, the 8th edition has been comprehensively updated and rewritten. Accessible, student-fri endly and truly international in its coverage, this edition has an impr oved structure and new material on methodology"--
Machine generated contents note: PART 1 CONCEPTS AND APPROACHES -- P olitical Concepts -- Comparative Approaches -- Comparative Methods -- P ART 2 STATES AND REGIMES -- The State -- Democracy -- Authoritarian Rul e -- PART 3 POLITICAL MOBILIZATION -- Political Culture -- Political Co mmunication -- Political Participation -- Elections and Voting -- Inter est Groups -- Political Parties -- PART 4 GOVERNMENT AND GOVERNANCE -- Constitutions and Law -- Multilevel Governance -- Legislatures -- The P olitical Executive -- Public Management and Administration -- PART 5 PU BLIC POLICY AND POLITICAL ECONOMY -- The Policy Process -- Political Ec onomy -- PART 1 CONCEPTS AND APPROACHES -- Political Concepts -- Compar ative Approaches -- Comparative Methods -- PART 2 STATES AND REGIMES -- The State -- Democracy -- Authoritarian Rule -- PART 3 POLITICAL MOBIL IZATION -- Political Culture -- Political Communication -- Political Pa rticipation -- Elections and Voting -- Interest Groups -- Political Par ties -- PART 4 GOVERNMENT AND GOVERNANCE -- Constitutions and Law -- Mu ltilevel Governance -- Legislatures -- The Political Executive -- Publi c Management and Administration -- PART 5 PUBLIC POLICY AND POLITICAL E CONOMY -- The Policy Process -- Political Economy.
Keywords: Comparative government